Novel CAD gene mutations in a boy with developmental and epileptic encephalopathy 50 with dramatic response to uridine therapy: a case report and a review of the literature - Lifen Duan; Lei Ye; Runxiu Yin; Ying Sun; Wei Yu; Yi Zhang; Haiyan Zhong; Xinhua Bao; Xin Tian (BMC, 2024)
Abstract Background Developmental and epileptic encephalopathy-50 (DEE-50) is a rare clinical condition believed to be caused by a mutation in the CAD gene and is associated with a bleak prognosis. CAD-related diseases have a wide range of clinical manifestations and other symptoms that may be easily overlooked. Like other rare diseases, the clinical manifestations and the treatment of DEE-50 necessitate further investigation. Case presentation A 1-year-old male patient presented with developmental delay, seizures, and anaemia at 3 months of age. He further developed refractory status epilepticus (SE), rapid deterioration of cognitive and motor function, and even became comatose at 5 months of age. Whole-exome sequencing of trios (WES-trios) revealed a compound heterozygous variant in the CAD gene, with one locus inherited from his father (c.1252C>T: p.Q418* nonsense mutation) and one from his mother (c.6628G>A: p.G2210S, missense mutation). This compound heterozygous CAD variant was unreported in the Human Gene Mutation Database. After uridine treatment, his cognitive faculties dramatically improved and he remained seizure-free. Forty two cases with CAD gene mutation reported in the literatures were reviewed. Among them, 90% had onset before 3 years of age, with average of 1.6±1.8 years old. The average age of diagnosis was 7.7 ± 10 years. The mortality rate was approximately 9.5%, with all reported deaths occurring in patients without uridine treatment. The clinical entity could be improved dramatically when the patient treated with uridine. Conclusions We present a boy with DEE 50 caused by novel CAD gene mutations and reviewed the clinical features of 42 patients reported previously. DEE 50 has early onset, refractory seizures, even status epilepticus leading to death, with favorable response to treatment with oral uridine. Early uridine treatment is recommended if CAD defect is suspected or genetically diagnosed. This study enhances the knowledge of DEE 50 and expands the spectrum of CAD gene mutations.